The Role of Cash Waqf Model in Education Development- Evidence from Afghanistan - Baryal, Baryalai; Mehraaein, Mahmood; Patang, Ghazi (Integrated Journal for Research in Arts and Humanities, 2022)
Cash waqf is a trust fund established with money to support services to mankind in the name of Allah. It is recognized that there is no ample study in the area of cash waqf. Again literature is very scanty relating to the cash waqf area, especially for the establishment of Islamic financial institutions for financing in education. This article aims to attempt to make an Innovative Financing education through Islamic Finance. In Afghanistan, most people do not get substantial education and there is a lack of financial support for the students in Afghanistan. We want to use cash waqf Islamic financial instruments to give efficient and sufficient education to Afghan people. we introduce this cash waqf model (CWM) or framework to help education in Afghanistan. This study has developed the (CWM) model as a source of financing for education in Afghanistan. This model is expected to provide financial services by using cash waqf funds for poor families to support their students to study. This model incorporates Musharakah, Murabaha, and mudarabah Islamic products to gain profit and support education. The methodology of this paper is qualitative research through document analysis of relevant references about cash waqf models. The general finding of this project shows that there is a possible structure for cash waqf instruments that can be implemented in the future for financing education in Afghanistan.